국내에서 ECOSTRESS 지표면 온도 및 증발산(PT-JPL) 자료의 검증 - 박기진; 김기영; 김찬영; 박종민; Park, Ki Jin; Kim, Ki Young; Kim, Chan Young; Park, Jong Min (KSCE Journal of Civil and Environmental Engineering Research, 2024)
The frequency of extreme weather events such as heavy and extreme rainfall has been increasing due to global climate change. Accordingly, it is essential to quantify hydrometeorological variables for efficient water resource management. Among the various hydro-meteorological variables, Land Surface Temperature (LST) and Evapotranspiration (ET) play key roles in understanding the interaction between the surface and the atmosphere. In Korea, LST and ET are mainly observed through ground-based stations, which also have limitation in obtaining data from ungauged watersheds, and thus, it hinders to estimate spatial behavior of LST and ET. Alternatively, remote sensing-based methods have been used to overcome the limitation of ground-based stations. In this study, we evaluated the applicability of the National Aeronautics and Space Administration's (NASA) ECOsystem Spaceborne Thermal Radiometer Experiment on Space Station (ECOSTRESS) LST and ET data estimated across Korea (from July 1, 2018 to December 31, 2022). For validation, we utilized NASA's MODerate Resolution Imaging Spectroradiometer (MODIS) data and eddy covariance flux tower observations managed by agencies under the Ministry of Environment of South Korea. Overall, results indicated that ECOSTRESS-based LSTs showed similar temporal trends (R: 0.47~0.73) to MODIS and ground-based observations. The index of agreement also showed a good agreement of ECOSTRESS-based LST with reference datasets (ranging from 0.82 to 0.91), although it also revealed distinctive uncertainties depending on the season. The ECOSTRESS-based ET demonstrated the capability to capture the temporal trends observed in MODIS and ground-based ET data, but higher Mean Absolute Error and Root Mean Square Error were also exhibited. This is likely due to the low acquisition rate of the ECOSTRESS data and environmental factors such as cooling effect of evapotranspiration, overestimation during the morning. This study suggests conducting additional validation of ECOSTRESS-based LST and ET, particularly in topographical and hydrological aspects. Such validation efforts could enhance the practical application of ECOSTRESS for estimating basin-scale LST and ET in Korea. 전 세계적인 기후변화의 영향으로 폭우 및 극한 강우 등 이상기후의 발생 빈도가 증가하는 추세이다. 이에 따른 효율적인 수자원 관리 대책 수립을 위해 수문기상인자를 정량화하는 것은 필수적이다. 다양한 수문기상인자 중 지표면 온도(Land Surface Temperature; LST)와 증발산(Evapotranspiration; ET)은 지표와 대기에서의 수문 및 에너지 순환을 이해하는 데 핵심적인 역할을 수행한다. 국내에서는 주로 지점 기반 관측 방법을 통해 LST와 ET를 관측하고 있지만, 이러한 방법은 미계측 유역에서의 자료 수득이 제한되며, 불균형한 관측소의 밀도로 인해 관측한 자료를 유역 단위 자료로 공간화할 수 없는 한계점이 존재한다. 이를 극복하기 위해 국내·외에서는 원격탐사를 기반으로 한 수문기상인자의 추정 방법을 활용하고 있다. 이에 본 연구에서는 2018년 7월 1일부터 2022년 12월 31일까지 국내를 대상으로 추정한 NASA (National Aeronautics and Space Administration)의 ECOSTRESS (ECOsystem Spaceborne Thermal Radiometer Experiment on Space Station) LST 및 ET 자료의 정확도를 평가하였다. 연구 과정에서 ECOSTRESS 자료의 비교 및 분석을 위해 기존 검증이 이루어진 NASA의 MODIS (MODerate Resolution Imaging Spectroradiometer) 자료와 환경부 산하 기관(홍수통제소 및 한국수자원조사기술원)에서 관리하는 에디 공분산 기반 플럭스 타워(Eddy covariance flux tower) 관측 자료를 활용하였다. 연구결과 ECOSTRESS LST는 MODIS 및 지점 자료(R: 0.47~0.73)와 유사한 시계열적 경향성을 보였다. Index of agreement 또한 0.82~0.91의 범위를 나타냈지만, 계절적 특성에 따라 뚜렷한 불확실성을 보였다. ECOSTRESS ET의 경우 전반적으로 MODIS 및 지점 자료와 유사한 시계열적 경향성을 나타냈지만, 평균절대오차(Mean Absolute Error) 및 평균제곱근오차(Root Mean Square Error)가 높게 나타났다. 이는 ECOSTRESS 자료의 수득률 및 환경적 요인(증산에 의한 Cooling effect, 오전 시간대 과대 산정 등)이 영향을 미친 것으로 파악된다. 추후 연구를 통해 이러한 문제점을 해결하고, 지형학적·수문 학적 검정 및 보정을 통해 실질적으로 국내에서 ECOSTRESS를 기반으로 한 유역 단위 LST, ET의 추정이 가능할 것으로 판단된다.